Studi Kasus: Pendekatan Klinis dan Evaluasi Terapi dalam Penanganan Hematuria pada Sapi Perah di Kecamatan Cigedug, Kabupaten Garut: Case Study: Clinical Approach and Therapy Evaluation in Handling Hematuria in Dairy Cows in Cigedug District, Garut Regency - Yusuf, Muchamad Ramadhan Ardhi; Hidayat, Yusep Saeful; Septiyani, Septiyani; Setyowati, Endang Yuni; Satrio, Faisal Amri (Fakultas Peternakan Universitas Jambi, 2025)
Background: The occurrence of various diseases in dairy cattle farms is the cause of low milk production in Indonesia. Hematuria or blood in the urine due to infectious and non-infectious diseases in dairy cattle is one of the causative factors. Objective: This case study aims to analyze the clinical approach in the diagnosis of hematuria in dairy cattle and evaluate the effectiveness of the therapy applied based on a case study in Cigedug District, Garut Regency. Method: This case study was conducted through anamnesis to obtain information, signals to identify the basic characteristics of dairy cattle, physical examination, and determination of diagnosis and prognosis, which were then followed by therapeutic management based on diagnostic findings. Results: A one-year-old female Friesian Holstein crossbreed dairy cow that had hematuria since one week before this examination appeared less active, had poor appetite, was trembling, had pale mucosa, a heart rate of 128 times per minute, a respiratory rate of 40 times per minute, and a temperature of 41.6 ºC. There was a hard tick infestation on the body and cage. After being injected with Tryponil® (diminazene aceturate and phenazone) via the intramuscular route, the cow's body temperature improved from 41.6 °C to 39.7 °C and hematuria was no longer visible 3 days after injection. Conclusion: A clinical approach that includes anamnesis, signaling, physical examination, and therapeutic management is effective in diagnosing and treating hematuria in dairy cows, as in the case study, where intramuscular administration of Tryponil® eliminated clinical symptoms and improved clinical condition within three days.